RECOVERY OF MICRO FINANCING FOR WOMEN AT BANK BTPN SYARIAH DURING COVID-19 - Trimulato Trimulato (IAIN Manado, 2021)
The purpose of this research is to savvy the development of distribution productive financing for women’s economic enterprises at Bank BTPN Syariah and to describe the form of recovery conducted by Bank BTPN Syariah for women’s economic due to the impact of covid-19. This research is library research, using several sources that are considered relevant to the research theme. The research is qualitative describing the financing for women’s empowerment. Analysis technique in this research is descriptive qualitative by describing development financing at Bank BTPN Syariah during Covid-19, and describing patterns restoring women’s economic empowerment by bank BTPN Syariah. The results of this study indicate a decline in financing at Bank BTPN Syariah period March 2020 to August 2020. Murabahah transaction has decreased to 22.16 percent, musharakahhas decreased to 55.82 percent, and qard has decreased to 3.90 percent. The recovery strategy for women’s economic, conducted by Bank BTPN Syariah in the midst of covid-19 is to provide financing relief to SMEs customers, restructuring, good communication with customers, training for customers, and improving digital services. Bank BTPN Syariah customers affected by the pandemic, that is why efforts are made to fulfil customer needs, and bank performance returns to be better.